(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Describes a problem of spiritually-moral education of the young generation, heirs of alash Kazakh media today. The author describes and analyzes the origins of spiritual culture of the Kazakh people, commit history ètnovospitaniâ current at all times. A huge role of the media in the dissemination, in raising and resolving pressing problems revealed by the author on the basis of an analysis of published articles from the pages of such well-known Republican publications like "Ajķyn", "Zhas Kazak", "Kazak adebieti», «zhas alash", "Kazakhstan-Zaman", "Tүrkìstan" in the Kazakh language. A detailed analysis of actual materials and their (media ’s) role in the upbringing of the spiritual culture of tolerance, in the formation of ideas gumannizma is invaluable, and in keeping with the theme reflected in this article.